2006
DOI: 10.1111/j.1365-2710.2006.00775.x
|View full text |Cite
|
Sign up to set email alerts
|

TPMT genotype and its clinical implication in renal transplant recipients with azathioprine treatment

Abstract: Our results, together with those of others pointing in the same direction, suggest that genotyping the major TPMT variant alleles may be a valuable tool in preventing AZA toxicity and optimization of immunosuppressive therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 29 publications
0
6
0
3
Order By: Relevance
“…Recently, genetic polymorphisms of TPMT and NUDT15 have been proposed to be involved with an increased risk of myelosuppression in patients treated with thiopurine drugs, including 6-MP and its prodrug, azathioprine. 4,8,9,14,15,18,19 To the authors' knowledge, this is the first study evaluating the common TPMT variant and all known loss-of-function NUDT15 variants in Thai pediatric ALL patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, genetic polymorphisms of TPMT and NUDT15 have been proposed to be involved with an increased risk of myelosuppression in patients treated with thiopurine drugs, including 6-MP and its prodrug, azathioprine. 4,8,9,14,15,18,19 To the authors' knowledge, this is the first study evaluating the common TPMT variant and all known loss-of-function NUDT15 variants in Thai pediatric ALL patients.…”
Section: Discussionmentioning
confidence: 99%
“…7 Several studies have demonstrated that individuals who carry these variant alleles may be at a higher risk of severe myelosuppression when treated with 6-MP or 6-MP derivatives. 7,8 In contrast to TPMT, NUDT15 genetic polymorphism is more common in Asian populations than in Caucasian populations. Phenotypes of more than 10 variant alleles of NUDT15 have been extensively characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Kurzawski et al [18] demonstrated that the number of HZ renal transplant patients (n=2, 15%) who experienced rejection were similar to WT (n=20, 20%). Amongst the 8 HZ renal transplant recipients in a study by Song et al, [19] there was a trend towards increased rejection in HZ (25%) as compared to WT patients (21.9%). In both studies, the starting AZA dose was not adjusted based on genotype, so the implications for a reduced AZA dose are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, a number of studies have indicated that there is a significant negative correlation between the intracellular concentration of TGNs and TPMT activity in erythrocytes [Lennard, 1990;] and TGN concentrations are associated with the efficacy and toxicity of thiopurines in various diseases including leukemia and IBD [Chrzanowska et al, 2006;Davison et al, 2006;de Boer et al, 2007;Dervieux et al, 1999;Dokmanovic et al, 2006;Evans et al, 1991;Gisbert, 2006;Lennard and Lilleyman, 1989;Lennard et al, 2006;Lennard et al, 1997;Morales et al, 2006;Schedel et al, 2006;Song et al, 2006].…”
Section: Genotype-phenotype Relationshipsmentioning
confidence: 99%